Gambaran Fungsi Perpustakaan Sekolah Luar Biasa Al-Faqih Bagi Anak Disabilitas di Kecamatan Tuah Madani Kota Pekanbaru - Hasnidar; Yuli Astuti (Perpustakaan Universitas Riau, 2023)
Disability refers to the limitations that a person has. Disabilities are influenced by the surrounding environment that is not yet disability-friendly. The library is a storehouse of knowledge. The library is a reading garden and has a function for children with disabilities. However, many children do not take advantage of the function of the library as a place of information. Children with disabilities rest more and do not focus on library use activities. The purpose of this study was to find out how the function of the library for children with disabilities at SLB Al-Faqih, Tuah Madani Pekanbaru is described. This research design uses qualitative methods. Data collection using interviews. The results showed that: 1) students have not utilized the library as a center for teaching and learning activities for education as stated in the school curriculum, 2) students have not been able to develop their creativity and imagination, and 3) students have not been able to position the library as a recreational place to fill their free time. The conclusion of this study is that the average school library function cannot be applied by students with disabilities.